2018
DOI: 10.18203/2394-6040.ijcmph20181234
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and economic determinants of adherence to iron intake among pregnant women in selected low and lower middle income countries in Asia: insights from a cross-country analyses of global demographic and health surveys

Abstract: Background: Anaemia is a global public health problem affecting around 800 million children and women worldwide. Anaemia, defined as a reduced haemoglobin concentration, is associated with increased peri-natal mortality, increased child morbidity and mortality, impaired mental development, impaired immune competence, increased susceptibility to lead poisoning, and decreased performance at work.Methods: This paper attempts to understand the determinants underlying iron intake in select countries in Asia using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
3
11
0
Order By: Relevance
“…Interestingly, our study found that adherence to iron supplementation was significantly associated with ownership of a television and/or radio, indicating higher likelihood of exposure to mass media. This was not surprising and aligned with previous studies that found exposure to mass media was significantly associated with adherence to iron supplementation and could be useful in improving adherence (38, 55). Mass media is the most effective way to spread health messages in low-resource areas, such as SSA (56).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, our study found that adherence to iron supplementation was significantly associated with ownership of a television and/or radio, indicating higher likelihood of exposure to mass media. This was not surprising and aligned with previous studies that found exposure to mass media was significantly associated with adherence to iron supplementation and could be useful in improving adherence (38, 55). Mass media is the most effective way to spread health messages in low-resource areas, such as SSA (56).…”
Section: Discussionsupporting
confidence: 89%
“…We investigated the following factors to assess whether they were associated with adherence to iron supplementation: number of antenatal care visits, pregnancy status, breastfeeding status, age, education status, marital status, wealth index status, place of residence, employment status, number of living children, household owning a radio, household owning a television, having a prenatal nurse during the most recent pregnancy that led to a birth, and a history of terminated pregnancy (36). Previous studies reported that these sociodemographic-economic factors affect women's adherence to iron supplementation in SSA (19, 28, 29, 32, 37, 38). Based on previous literature, we recategorized the wealth index from 5 quintiles into 3 categories by combining poorest and poorer into one category (called “poor”); middle wealth level into the second category (called “middle”); and richer and richest into the third category (called “rich”), as previous researchers have done (39, 40).…”
Section: Methodsmentioning
confidence: 99%
“…Pregnant women who were exposed to media were 1.3 times more likely to take iron tablets as compared to their counterparts. This study was supported by a study in Asia (30). This is due to the fact that different maternal health services including the importance of taking iron during pregnancy is frequently given for the community through mass media.…”
Section: Discussionmentioning
confidence: 69%
“…36 An investigation in South Africa also suggested that, compliance was thought to be influenced by the regular good attendance of antenatal care clinic service. 37 The result of meta-analysis showed pregnant women who had early registered for antenatal care during pregnancy was three times more likely to have compliance with IFAS in relation to those women who had late registered for antenatal care. Similarity study done in Malawi reported, attending antenatal care during the first trimester were significantly associated with increased odds of taking iron supplementation for 90 days or more during pregnancy.…”
Section: Discussionmentioning
confidence: 99%